Anthroposophy in the antipodes : a lived spirituality in New Zealand 1902-1960s : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Religious Studies at Massey University, Manawatu, New Zealand - Turbott, Garth John (Massey University, 2013)
Anthroposophy is the spiritual philosophy and pathway (the “spirituality”) taught by the Austrian philosopher and seer Rudolf Steiner, from 1902 until his death in 1925. Since then it has become established as a worldwide movement, with particular strength in German speaking countries, and it has developed a small but significant following in New Zealand. This began in 1902, after New Zealand’s first Anthroposophist heard Steiner lecture during a trip to Leipzig, and in 1933 led to the establishment of the Anthroposophical Society in New Zealand, linked to the parent body the General Anthroposophical Society in Dornach, Switzerland. This is the first substantial academic study of Anthroposophy in New Zealand and traces its growth from 1902 until the 1960s. It examines the development of the core of the movement, the Anthroposophical Society in New Zealand, and also of the daughter movements, Steiner childhood education, biodynamic gardening and farming, and anthroposophical medicine. Together these comprise the broad anthroposophical movement in this country. Many of the early New Zealand Anthroposophists came from an Anglican background. Most were middle-class and well-educated, farmers, business people, artisans or professionals. Although relatively small in number, the anthroposophical movement has had a significant influence in the arts, education, horticulture and agriculture, and the practice of complementary medicine in New Zealand. The presence of Anthroposophy, and the influence exerted by the broad anthroposophical movement, adds weight to the argument that European New Zealand society was not exclusively as materialist and secular as was alleged in much historiography of the second half of the twentieth century.
Keywords: Anthroposophy; Anthroposophists, New Zealand; Rudolf Steiner; Anthroposophical movement